"De trem pra Montes Claros": representações do sertão norte-mineiro nas canções do Grupo Raízes (1973-1983) - Durães, Mary Aparecida de Alencar (2010)
This research analyzes representations of the backlands (sertão) in the northern part of the state of Minas Gerais, Brazil in the songs of the band Grupo Raizes produced between 1973 and 1983. It deals with the musical and social trajectory of the group, situated between the city and the country, expressing representations of the Northern Minas sertão. This band made regional music and enjoyed success in various Brazilian cities, releasing their first LP in São Paulo, the city in which the group was formed. Its members were students from São Paulo, the Northeast and the north of Minas, and concentrated in their songs on aspects of the culture of the north of Minas, including prayers, apparitions, legends, yarns, social banditry, and various aspects of popular religious and social festivals,. Given the cultural diversity of the sertão, this thesis also engages in a study of the concept of the sertão and its representations. Through an analysis of the elements sertão, representation and song, it approaches aspects of the life of the inhabitants of the sertão, their experiences, resistance and conflicts. It aims to understand how the sertão was thought and lived in the North of the state of Minas Gerais. This study is based on a bibliographic and musical research, involving interviews, analysis of images and photographs. It is a study in cultural history, delineating cultural practices, social representations, identities, social experiences, modes of being, of expressing and living. From this research it was possible to conclude that the Grupo Raizes sang the sertão of the north of Minas Gerais and its identities and made music engaged with the purpose of singing who we are . In this musical universe, the group distinguished itself in the field of popular Brazilian music, moving between the rural and the urban, pop music and the regional, singing poetically and with sensibility the sertão the North of Minas.